2002
DOI: 10.4049/jimmunol.169.1.587
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Autoantibody Production Is Limited in Nonautoimmune Mice

Abstract: Many individuals develop a single or a few brief episodes of autoimmunity from which they recover. Mechanisms that quell pathologic autoimmunity following such a breakdown of self-tolerance are not clearly understood. In this study, we show that in nonautoimmune mice, dsDNA-specific autoreactive B cells exist but remain inactive. This state of inactivation in dsDNA-specific B cells could be disrupted by autoreactive Th cells; in this case T cells that react with peptides from the VH region of anti-DNA Abs (her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
66
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 42 publications
1
66
0
Order By: Relevance
“…It is important to emphasize that a rigorous characterization of the exquisite T-cell epitopes that activate suppressor T cells, versus those that stimulate pathogenic Th cells, in humans is crucial to ensure that we do not run into premature disappointment, as seen in some other antigen therapy trials. Complicating the selection of peptides for treatment, our murine studies suggest that suppressor and Th-cell epitopes might colocalize or overlap [20], as if nature has done a fine Most T-cell lines generated from immunized BWF1 mice are CD4 C Th cells that promote anti-DNA antibody formation in vitro [9]. By contrast, although CWF1 mice develop CD4 C Th cells during initial immunizations, most T-cell lines, including CD8 C cells, CD4 C CD25 C Treg cells and NKT cells, generated from CWF1 mice recovering from disease suppress anti-DNA antibody production by lupus (BWF1) B cells [9,19,20].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to emphasize that a rigorous characterization of the exquisite T-cell epitopes that activate suppressor T cells, versus those that stimulate pathogenic Th cells, in humans is crucial to ensure that we do not run into premature disappointment, as seen in some other antigen therapy trials. Complicating the selection of peptides for treatment, our murine studies suggest that suppressor and Th-cell epitopes might colocalize or overlap [20], as if nature has done a fine Most T-cell lines generated from immunized BWF1 mice are CD4 C Th cells that promote anti-DNA antibody formation in vitro [9]. By contrast, although CWF1 mice develop CD4 C Th cells during initial immunizations, most T-cell lines, including CD8 C cells, CD4 C CD25 C Treg cells and NKT cells, generated from CWF1 mice recovering from disease suppress anti-DNA antibody production by lupus (BWF1) B cells [9,19,20].…”
mentioning
confidence: 99%
“…Serendipitous discoveries or deliberate attempts have led to the identification of animal models that appear to recapitulate these various steps or stages of disease ( Figure 2). For example, BALB/c mice immunized with a DNA surrogate peptide develop autoantibodies and extensive immune deposition but have no renal inflammation [7], whereas BALB/c mice injected with the hydrocarbon oil pristane develop immune deposition and a limited kidney inflammation but no kidney failure [8,9]. However, genetically lupus-prone mouse strains develop lethal renal disease spontaneously, with strain-dependent variation in disease patterns and severity [4,10].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These studies provide a rationale to develop "universally tolerogenic" epitopes for antigen-specific lupus treatment [8]. Recent studies from Erikson and Singh's laboratories also showed that the anergy of anti--dsDNA B cells in non-autoimmune mice could be reversed by the provision of T cell help [58,61], although the induction of autoAb synthesis and renal pathology appears to be mild and transitory. Our previous studies have indicated that T cells from lupus-prone MRL lpr/lpr 2-12 Tg mice can help B cells of non-autoimmune origin to initiate an anti-snRNP response [73].…”
Section: Cd4 + T Cells and Autoreactive B Cell Activationmentioning
confidence: 99%